(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2015)
The article is devoted to research of Cyril Razumovsky and Peter Kalnyshevsky coverage in the context of the historical period of decline Cossacks. The article by using historical sources and artistic works by Ukrainian writers considered figures of last Cossack hetman and last koshovjy, attempts to comparable characteristics of these figures.